The eurozone crisis, German hegemony and labour market reform in the GIPS countries. Issue 2 (17th April 2017) - Currie, Denise; Teague, Paul
Abstract: This article argues that the eurozone crisis has led to Germany hegemony, a feature of which has been complete resistance to a genuinely European solution to the crisis. German political leaders have sought to make the eurozone a more stable currency area by demanding far reaching labour market adjustment in the debtor countries of Greece, Ireland, Portugal and Spain, GIPS countries. This article assesses why Germany's leaders elected to act as a coercive hegemon and examines the labour market reform pathways being travelled by GIPS countries. It argues that the austerity regime enacted under German hegemony has obliged the GIPS countries to introduce important labour market reforms. However, these reforms have not threatened the integrity of established national systems of industrial relations. As a result a Euro war of attrition has opened up between the European core and periphery.